RESPON TANAMAN TOMAT (Lycopesicum esculentum MILL.) TERHADAP APLIKASI KOMPOS DAUN AKASIA - Davit Sartono; Wardati Wardati; Isnain Isnain (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
1. Mahasiswa Fakultas Pertanian Universitas Riau2. Dosen Fakultas Pertanian Universitas Riau  Tomatoes are seasonal vegetable crops that consumed in a fresh food and contain vitamins and minerals. In 2015 tomato production in Riau Province decreased by 27 tons from 2014 due to the conversion of agricultural land and unproductive land. This study aims to determine the effect of acacia leaf compost application and get the best dose that can increase the growth and yield of tomato plants. Field experiments were performed using a completely non factorial randomized design (RAL) with three replications. The doses of acacia leaf compost used were 10 ton.ha-1, 20 ton.ha-1  dan 30 ton.ha-1. The data obtained were analyzed by analysis of variance (ANOVA) using SAS application program. The data were significantly different then tested further by testing duncan's new multiple range test (DNMRT) at 5% level. Parameters observed were plant height, flowering age, age of first harvest, number of fruit, weight per fruit, fruit twining and fruit weight per plant. The results showed that acacia leaf compost treatment did not give significant effect to plant height parameters, flowering age, harvest age, weight per fruit, and fruit girth. Parameters that show the real effect of the number of fruit and weight of fruit per plant. Keywords : Acacia leaf compos and tomatoes